Do Product Characteristics Affect Customers’ Participation in Virtual Brand Communities? An Empirical Study - ShiYong, Zheng; JiaYing, Li; HaiJian, Wang; Dukhaykh, Suad; Lei, Wang; BiQing, Li; Jie, Peng (Frontiers in Psychology, 2022)
The virtual brand community has become an important marketing tool for companies. A successful brand community marketing strategy should attract a large number of consumers. Although past studies have revealed consumer motivations for participating in virtual brand communities, they fail to answer an important question: Why is it so easy for some virtual brand communities to attract users while others have such difficulty? In this study, product characteristics are hypothesized to be important factors that determine consumer motivation to participate in brand communities. Product characteristics (e.g., product complexity, product symbolism and product satisfaction) can directly affect how actively consumers participate in brand communities. The results of questionnaires show that product complexity, product symbolism and product satisfaction have a positive influence on consumers’ willingness to participate in brand communities. Notably, the duration of product use has a regulating effect on the influence of product satisfaction and product symbolism. A long period of product use weakens the influence of product satisfaction on consumers’ willingness to participate in brand communities. On the contrary, a long period of product use strengthens the influence of product symbolism on consumers’ willingness to participate in brand communities. This study enriches the literature on brand community participation and has implications for companies that aim to utilize brand communities for marketing.